2008
DOI: 10.1590/s0036-46652008000100003
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of GUAVA, Psidium guajava Linnaeus, leaf extracts on diarrhea-causing enteric bacteria isolated from Seabob shrimp, Xiphopenaeus kroyeri (Heller)

Abstract: SUMMARYGuava leaf tea of Psidium guajava Linnaeus is commonly used as a medicine against gastroenteritis and child diarrhea by those who cannot afford or do not have access to antibiotics. This study screened the antimicrobial effect of essential oils and methanol, hexane, ethyl acetate extracts from guava leaves. The extracts were tested against diarrhea-causing bacteria: Staphylococcus aureus, Salmonella spp. and Escherichia coli. Strains that were screened included isolates from seabob shrimp, Xiphopenaeus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
36
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 17 publications
10
36
0
7
Order By: Relevance
“…This effect could be attributed to the structure of gram negative bacterial cell wall that provides a level of intrinsic resistance to certain hydrophilic substances and thus preventing the penetration of active materials in water extracts into the bacterial cell. This could provide an explanation for our results [10,21]. Inhibitory effects of acetone leaf extracts showed similar results to those of other studies [6,10,22].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This effect could be attributed to the structure of gram negative bacterial cell wall that provides a level of intrinsic resistance to certain hydrophilic substances and thus preventing the penetration of active materials in water extracts into the bacterial cell. This could provide an explanation for our results [10,21]. Inhibitory effects of acetone leaf extracts showed similar results to those of other studies [6,10,22].…”
Section: Discussionsupporting
confidence: 92%
“…This could provide an explanation for our results [10,21]. Inhibitory effects of acetone leaf extracts showed similar results to those of other studies [6,10,22].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As shown by GONÇALVES et al 18 and NASCIMENTO et al 31 , S. aureus has been inhibited by extracts prepared from a variety of phanerogams. Likewise, VIEIRA et al 42 found S. aureus to be sensitive to guava leaf extracts in a study testing medicinal plants against bacteria causing diarrhea in children.…”
Section: Resultsmentioning
confidence: 88%
“…30 The essential oil from leaf extract of P. guajava exhibited the inhibitory activity towards S. aureus and Salmonella species. 31 Pelegrini et al 32 isolated the peptide Pg-AMP1 from the seeds of P. guajava. Pg-AMP1 showed growth reduction in Klebsiella sp.…”
Section: Antimicrobial Activitymentioning
confidence: 99%